2007
DOI: 10.1002/adma.200601285
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Chain Orientation and Interchain π‐Interaction in Conjugated Polymer Thin Films: Direct Measurements of the Air and Substrate Interfaces by Near‐Edge X‐ray Absorption Spectroscopy

Abstract: The orientation and packing of semiconducting polymer chains at film interfaces crucially affects charge injection and transport at those interfaces. Although X-ray diffraction techniques have been used extensively as a structural probe, they are not particularly sensitive to these interfaces. Near-edge X-ray absorption fine-structure spectroscopy (NEXAFS), on the other hand, is sensitive to surface orientation and has been applied to investigate polymer structures, for example, in polyimide, [1] polyfluorene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 42 publications
7
74
2
Order By: Relevance
“…39 Our model suggests that interfaces inhibit the formation of crystallites and that the polymer/dielectric interface is approximately 30% as crystalline as the bulk in films spun on OTS and 20% as crystalline in films on bare silicon oxide. As discussed above, the bulk crystallinity is found to be almost equal for the two surface treatments, in agreement with our hypothesis of a three-layer model in which the interfacial chemistry only affects crystallization in a thin layer in close proximity to that interface.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…39 Our model suggests that interfaces inhibit the formation of crystallites and that the polymer/dielectric interface is approximately 30% as crystalline as the bulk in films spun on OTS and 20% as crystalline in films on bare silicon oxide. As discussed above, the bulk crystallinity is found to be almost equal for the two surface treatments, in agreement with our hypothesis of a three-layer model in which the interfacial chemistry only affects crystallization in a thin layer in close proximity to that interface.…”
Section: Resultsmentioning
confidence: 78%
“…As discussed above, the bulk crystallinity is found to be almost equal for the two surface treatments, in agreement with our hypothesis of a three-layer model in which the interfacial chemistry only affects crystallization in a thin layer in close proximity to that interface. Although contradicting results have been reported as to the degree of structural order at the polymer/air interface relative to the bulk in thin films of P3HT, [39][40][41][42][43] it has been suggested that a thin disordered region exists at the polymer/air interface as well. 39 Ho et al 39 used near-edge X-ray absorption finestructure spectroscopy (NEXAFS) to demonstrate disorder in both the thiophene ring orientations and hexyl side chains in thin films of regioregular P3HT within the technique's $2.5 nm probing depth of the polymer/air interface.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…38,39 In addition, techniques are continually emerging to probe organic material interfacial region, including second harmonic and sum frequency generation spectroscopy, 40,41 angle resolved ultraviolet photoelectron spectroscopy, 42 various X-ray scattering techniques, 43,44 metastable-atom electron spectroscopy, 45 and near edge X-ray absorption fine structure (NEXAFS). 46,47 NEXAFS provides two unique measurement capabilities that complement these other techniques including (1) a high intensity synchrotron source allowing for monochromatic incident excitation and enabling enhanced peak resolution, and (2) polarized excitation enabling investigation of bond orientation. NEXAFS has proven useful at monitoring organization of self-assembled monolayers, 48,49 interfacial composition in lithographic polymers, 8,50−52 chemistry in polymeric materials, 53,54 chemical modification of polymeric surfaces, 55 as well as the near surface composition and orientation of block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The structural features of CPE surfaces are therefore of critical importance to better understand device function and to provide a basis for rational molecular design. Neutral conjugated polymers spontaneously organize from solution upon deposition [9,10] and the degree of order can be influenced by the deposition method, [11] solvent, [12,13] and substrate characteristics. [14] Critical parameters such as charge carrier mobility and emission efficiencies strongly depend on the resulting distance and orientation between the optoelectronic units.…”
mentioning
confidence: 99%